Do Metastatic Kidney Cancer Patients Benefit From Cytoreductive Nephrectomy? A Real-World Retrospective Study From the SEER Database - Li, Cheng; Wang, Ruiliang; Ma, Wenchao; Liu, Shenghua; Yao, Xudong (Frontiers in Surgery, 2021)
Introduction: The benefit of cytoreductive nephrectomy (CN) for metastatic kidney cancer has been challenged recently. We aim to evaluate the prognostic roles of surgical resection of primary tumor site for metastatic kidney cancer under a real world setting. Materials and methods: The Surveillance, Epidemiology and End Results (SEER) database data (2010-2015), and overall survival (OS) and cancer-specific survival (CSS), were evaluated using the Cox proportional hazards regression model. One-to-one matching using the propensity score were used to estimate and compare survival rates. Results: The SEER data contains 8932 patients from 2010 to 2015 were included, of whom 61.7% underwent CN while 38.2% did not receive any surgery. The median survival month for patient without surgery was 4 months and for patient with surgery was 19 months. Multivariate analysis showed surgical resection of the primary tumor site was an independent favorable predictor for both OS and CSS (all p<0.001) both in the original and the matching cohort. Conclusions: In the era of target therapy, CN might still a vital method to treat metastatic kidney cancer.